The relationship between foreign direct investment in manufacturing sector and the interest rate, inflation rate and investment incentives - Ab Rashid, Mohd Elfee (2004)
This study attempt to examine the relationship between the Foreign Direct Investment in manufacturing sector and interest rate, inflation rate and investment incentives. The data for this study is taken on yearly basis, which covers the period of twenty years (from 1983-2002). By using the regression and correlation analysis, two alternate hypothesis were developed. First hypothesis mentioned that interest rate, inflation rate and investment incentives are significant explanatory variable for foreign investment inflow. Second, foreign direct investment is dependent on interest rate, inflation rate and investment incentives. Besides, coefficient of determination and coefficient of correlation were used to quantify the relationship between the dependent variable and independent variables. Consistent to the hypothesized, empirical evidences from this study revealed that there is significant relationship between foreign direct investment and interest rate, inflation rate and investment incentives.